Avaliação do efeito antioxidante de extratos naturais na estabilidade oxidativa de biodiesel - Freitas, João Paulo Almeida (2018)
The production and use of biodiesel, encouraged, among others, by the environmental issue, have been growing notably over the years. In Brazil, most of it is produced from soybean oil, followed by animal fats and cottonseed oil. Since the fiber is the main product of cotton, cottonseed oil as a source of biodiesel adds value this kind of crop. These raw materials have in their composition unsaturated fatty acids, what makes biodiesel susceptible to oxidation, which impairs the process of transportation, storage and use. One possible way to reduce such process is by using antioxidant additives. Synthetic antioxidants are commercially used which, despite their efficacy, have limitations due to their non-biodegradability and toxicity. In this context, natural antioxidants are emerging, which have been studied as possible substituents for synthetic antioxidants and thus make biodiesel an even more sustainable and less polluting source of energy. Moreover, the use of more than one antioxidant simultaneously can result in positive synergy, potentiating the antioxidant activity, in addition to reduce the amount used and, consequently, increasing the profitability of the biofuel. The objective of this work was to evaluate the antioxidant effect of plant extracts - catechin, curcumin and quercetin - on the oxidative stability of methyl biodiesel from cottonseed oil. To do so, the performance of each additive was assessed individually and in binary and ternary combinations for different concentrations in biodiesel – 1000, 2000 and 3000 ppm – by using simplex centroid augmented mixture experiment design . The biodiesel was synthesized by the methyl route using potassium hydroxide as catalyst and characterized in kinematic viscosity, water content, cold filter plugging point, acid value, oxidative stability and ester content. To evaluate the antioxidant potential of the extracts, the synthetic antioxidant BHA was used as reference. In order to evaluate the combined effect of the extracts, the experimental design of the centroid simplex type was used. Statistical analysis was performed using Statistica software version 10.0 with 95% confidence. The results were analyzed in terms of Pareto graph, response surface, contours surface and analysis of variance. The synthesized biodiesel’s properties resulted in satisfactory values and in general within the technical specifications. The oxidative stability was below the minimum established in law as expected, evidencing the need of antioxidants. Regarding the antioxidant action of the extracts, all of them presented antioxidant power for the biodiesel studied, also catechin and quercetin were more efficient than BHA. By increasing the concentration of extracts, the biodiesel stability also increased for all cases. When used in combination, the extracts showed statistically significant synergy only for the 1000 ppm design with the cubic response model. 2000 and 3000 ppm designs resulted in linear model, since the interactions were not significant. The designs presented small relative error, evidencing the good adjustment of the data, proven by the representative experiments, which also resulted in small errors.